Neural Processing of Repetition and Non-Repetition Grammars in 7- and 9-Month-Old Infants - Wagner, Jennifer B.; Fox, Sharon E.; Tager-Flusberg, Helen; Nelson, Charles A. (Frontiers in Psychology, 2011)
An essential aspect of infant language development involves the extraction of meaningful information from a continuous stream of auditory input. Studies have identified early abilities to differentiate auditory input along various dimensions, including the presence or absence of structural regularities. In newborn infants, frontal and temporal regions were found to respond differentially to these regularities (Gervain et al., 2008), and in order to examine the development of this abstract rule-learning we presented 7- and 9-month-old infants with syllables containing an ABB pattern (e.g., “balolo”) or an ABC pattern (e.g., “baloti”) and measured activity in left and right lateral brain regions using near-infrared spectroscopy (NIRS). While prior newborn work found increases in oxyhemoglobin (oxyHb) activity in response to ABB blocks as compared to ABC blocks in anterior regions, 7- and 9-month-olds showed no differentiation between grammars in oxyHb. However, changes in deoxyhemoglobin (deoxyHb) pointed to a developmental shift, whereby 7-month-olds showed deoxyHb responding significantly different from zero for ABB blocks, but not ABC blocks, and 9-month-olds showed the opposite pattern, with deoxyHb responding significantly different from zero for the ABC blocks but not the ABB blocks. DeoxyHb responses were more pronounced over anterior regions. A grammar by time interaction also illustrated that during the early blocks, deoxyHb was significantly greater to ABC than in later blocks, but there was no change in ABB activation over time. The shift from stronger activation to ABB in newborns (Gervain et al., 2008) and 7-month-olds in the present study to stronger activation to ABC by 9-month-olds here is discussed in terms of changes in stimulus salience and novelty preference over the first year of life. The present discussion also highlights the importance of future work exploring the coupling between oxyHb and deoxyHb activation in infant NIRS studies.